Formononetin Attenuates Renal Tubular Injury and Mitochondrial Damage in Diabetic Nephropathy Partly via Regulating Sirt1/PGC-1α Pathway - Huang, Qunwei; Chen, Hongbo; Yin, Kai; Shen, Yilan; Lin, Kanghong; Guo, Xieyi; Zhang, Xiang; Wang, Niansong; Xin, Wenfeng; Xu, Youhua; Gui, Dingkun (Frontiers in Pharmacology, 2022)
Mitochondrial abnormality is one of the main factors of tubular injury in diabetic nephropathy (DN). Formononetin (FMN), a novel isoflavonoid isolated from Astragalus membranaceus, has diverse pharmacological activities. However, the beneficial effects of FMN on renal tubular impairment and mitochondrial dysfunction in DN have yet to be studied. In this study, we performed in vivo tests in Streptozotocin (STZ) -induced diabetic rats to explore the therapeutic effects of FMN on DN. We demonstrated that FMN could ameliorate albuminuria and renal histopathology. FMN attenuated renal tubular cells apoptosis, mitochondrial fragmentation and restored expression of mitochondrial dynamics-associated proteins, such as Drp1, Fis1 and Mfn2, as well as apoptosis-related proteins, such as Bax, Bcl-2 and cleaved-caspase-3. Moreover, FMN upregulated the protein expression of Sirt1 and PGC-1α in diabetic kidneys. In vitro studies further demonstrated that FMN could inhibit high glucose-induced apoptosis of HK-2 cells. FMN also reduced the production of mitochondrial superoxide and alleviated mitochondrial membrane potential (MMP) loss. Furthermore, FMN partially restored the protein expression of Drp1, Fis1 and Mfn2, Bax, Bcl-2, cleaved-caspase-3, Sirt1 and PGC-1α in HK-2 cells exposure to high glucose. In conclusion, FMN could attenuate renal tubular injury and mitochondrial damage in DN partly by regulating Sirt1/PGC-1α pathway.